Optimization of ionic liquid-based aqueous two-phase system for partial purification of bacteriocin-like inhibitory substance from Enterococcus faecium CC2 and its inhibitory activity against Streptococcus mutans - Ng, Zhang Jin; Ng, Hui Suan; Kee, Phei Er; Gan, Chee-Yuen; Ahmad Mokhtar, Ana Masara; Abu Zarin, Mazni; Lee, Chee Keong; Tan, Joo Shun; Lan, John Chi-Wei (Elsevier, 2024)
Background: Bacteriocin-like inhibitory substance (BLIS) demonstrates potent inhibitory effect against oral pathogens. To apply in oral care products, high purity of BLIS is required in view of the safety and effectiveness in the application. Therefore, aqueous two-phase systems (ATPS) are introduced for the recovery and purification of BLIS. Methods: The optimization of ionic liquid-based ATPS (ILATPS) for the purification of BLIS from Enterococcus faecium CC2 was performed using response surface methodology (RSM). The partially purified BLIS was then identified, and the inhibitory effect against Streptococcus mutans UKMCC1019 was assessed. Significant Findings: ILATPS with a pH of 7 at a temperature of 40 °C, comprising of 10 % (w/w) fermentation broth, 15 % (w/w) 1‑butyl‑3-methylimidazolium tetrafluoroborate, (Bmim)BF4, 12.5 % (w/w) sodium citrate and 3 % (w/w) sodium chloride, resulted in the optimum purification factor of 4.406, recovery yield of 67.213 % and partition coefficient of 4.852. The BLIS was identified as enterocin CC2, with a molecular size of approximately 5.5–6 kDa. Furthermore, the partially purified BLIS at a concentration of 1.00 mg/mL demonstrated effective growth inhibition against S. mutans UKMCC1019. The ILATPS was shown to be a potential technology to enhance the purity of BLIS from E. faecium CC2.